P606 Adherence to endoscopic surveillance guidelines for advanced lesions and colorectal cancer in Inflammatory Bowel Disease in Spain: a collaborative study of AEG and GETECCU. (27th May 2021) - Ballester Ferré, M P; Mesonero, F; Flórez-Diez, P; Gómez, C; Fuentes-Valenzuela, E; Martín, N; Senosiain, C; Vela, M; Fernández-Clotet, A; Pérez, P; Rubín de Célix, C; Calviño-Suárez, C; et al.
Abstract: Background: Patients with colon Inflammatory Bowel Disease (IBD) have a higher risk of colorectal cancer (CRC) than general population. Current guidelines establish endoscopic surveillance recommendations; however, epidemiological studies show poor compliance. The main aim of our study was to analyse adherence to endoscopic surveillance guidelines. Secondary aim was to evaluate the prevalence and time-to advanced lesions or CRC. Methods: Retrospective multicentre study of patients with IBD followed-up in the participating centres between 2005 and 2020, who were diagnosed of IBD between 2005 and 2008, with criteria for CRC surveillance. Patients with CRC before IBD diagnosis were excluded. The ECCO 2013–2017 guidelines were used to evaluate adherence. Adenomatous lesions with >25% of villous component, >1cm or with high-grade dysplasia or serrated lesions >1cm or with any degree of dysplasia were considered advanced lesions. Software used for all analysis was R in its 3.6.1 version. Normality was checked with the Shapiro-Wilks test. Mean comparison was carried out using t-Student test while normality assumptions held true, otherwise, Mann-Whitney test. Time-to advanced lesions or CRC event between patients that had adherence to ECCO guidelines versus those who did not was performed through Kaplan-Meier and Log-rank test. P-values below 0.05 were considered significant. Results: A total of 1004 (713 Ulcerative Colitis, 252 Crohn's disease and 39 Indeterminate Colitis; 52% male) patients from 25 centres were recruited with a median age of 36 (26–47) years. 87% of all patients were included in the endoscopic surveillance programme. The main reasons for non-inclusion were the absence of indication by the physician (38%) and the presence of inflammatory activity (37%). Adherence to the first or subsequent surveillance colonoscopies was 45% and 61%, respectively, with a total adherence rate of 32%. Prevalence of advanced lesions or CRC was 4% and 7 cases of CRC were detected. Time-to-detection of these lesions since IBD diagnosis was significantly longer in non-adherent patients (13.4 + 1.3 vs 13.04 + 1.7; p<0.001). Adherence was associated to a higher detection of advanced lesions or CRC compared to non-adherent patients (HR: 1.97; IC: 1.02–3.79; p=0.043) (Figure 1). Conclusion: Adherence to ECCO guidelines for endoscopic surveillance is low in this Southern European population. A higher and earlier detection of advanced lesions or CRC was identified in the adherent group. The results of this study highlight the need to improve compliance with the recommendations to obtain better outcomes.